“HOMOSSEXUALIDADE É...”: discursos de professores e professoras de Ciências sobre o tema da homossexualidade. - CUNHA, Daniel Barcelos da (2019)
This research sought to analyze discourses about homosexuality of Science teachers from Grade 6 to 9 at a city run school in São Luís – MA. For this, we aimed to comprehend teachers’ conceptions regarding homosexuality and their approaches in Science classes; to verify how they perceive the presence of the given theme at school; and problematize the importance of discussing the theme, with theoretical-methodological contributions from Cultural Studies in Education. We conducted semi-structured interviews with ten teachers from schools of the Nucleus Itaqui/Bacanga. The interviews were recorded, transcribed, and submitted to content analysis, which supported the build-up of six analytical categories: teachers’ conceptions about homosexuality; perceptions about the homosexual subject; presence of the theme at school; perceptions about homophobia; what they would say about the theme in a Science class; and how they would discuss the theme in their classes. After the analysis, it was possible to perceive that the biologicist bias regarding the theme is significant, with homosexuality being related to biological and genetic determinisms, or acquired from the environment, such as from raising or traumas related to sexual abuse or disappointment in love, and related to attraction and restricted sexual practice. However, other discourses evidenced the perception of homosexuality as a sexual-affective condition. Homosexuality in school is perceived more in relation to boys, as a consequence from effeminate behavior, for example, whilst lesbian girls are not perceived as such. School’s normalizing characteristic is demonstrated by the silencing of the theme in Science classes, and by the attempt to control those students who have subversive behavior, which draw teachers’ attention. Those students are attempted to be controlled as a supposition that, only this way, they will be respected. Some teachers would approach the theme in ways that lead to deconstruction of distorted visions, stimulating students to put themselves in other people’s places. By performing this study, it was possible to perceive that despite some teachers having a more conservative vision, others consider the importance of bringing the theme to Science classes in order to fight prejudices, although such approach may not be a reality yet. Thus, given the current scenario, we see the possibility of some teachers developing a work of resistance, aiming respect, alterity, and deconstruction of prejudices.